Leveraging AlphaFold models to predict androgenic effects of endocrine-disrupting chemicals through zebrafish androgen receptor analysis - Karim, Md Adnan; Park, Chang Gyun; Cho, Hyunki; Sebastian, Annmariya Elayanithottathil; Ryu, Chang Seon; Yoon, Juyong; Kim, Young Jun (Toxicology mechanisms and methods, 2025)
The androgen receptor (AR) activation by androgens is vital for tissue development, sexual differentiation, and reproductive attributes in zebrafish (Danio rerio). However, our understanding of the molecular mechanisms behind their activation remains limited. In this study, we employed both ab initio (AlphaFold) and homology (SWISS-MODEL) structure models of zebrafish androgen receptor ligand-binding domain (zAR-LBD) to explore the binding specificity, binding affinity, and molecular interactions of endogenous hormones (testosterone (T), 11-ketotestosterone (11-KT), and dihydrotestosterone (DHT)) in a computational simulation. Molecular docking analysis showed that both structures formed the same interactions and similar patterns of binding energy with androgens. Molecular Dynamics (MD) simulation analysis revealed that hydrogen bond occupancy aligned with in vitro findings related to androgenic effect. When comparing complexes modeled by SWISS-MODEL and AlphaFold, significant differences were observed in root mean square deviation (RMSD) and root mean square fluctuations (RMSF). The AlphaFold structures also exhibited a clear separation between ligands in principal component analysis. Further correlation analysis between in silico features and in vitro EC50 values identified MMPBSA energies as the most significant contributors to ligand-specific variance in the in silico complexes (p < 0.05). Overall, this integrative approach offers significant insights into the molecular mechanisms underlying zebrafish AR activity. 3D structures of zAR-LBD were generated using ab initio prediction and homology modeling programs.The AlphaFold model demonstrated greater structural stability, which significantly impacted the accuracy, reliability, and reproducibility of data predictions compared to the SWISS-MODEL.Hydrogen bond patterns in the AlphaFold structure were consistent with in vitro androgenic effects.The integrated in vitro and in silico approaches holds potential as a complementary tool for screening androgenic EDCs. 3D structures of zAR-LBD were generated using ab initio prediction and homology modeling programs. The AlphaFold model demonstrated greater structural stability, which significantly impacted the accuracy, reliability, and reproducibility of data predictions compared to the SWISS-MODEL. Hydrogen bond patterns in the AlphaFold structure were consistent with in vitro androgenic effects. The integrated in vitro and in silico approaches holds potential as a complementary tool for screening androgenic EDCs.
Gesehen am 12.08.2025